Cervical osteomyelitis caused by Pseudomonas cepacia in an intravenous-drug abuser. - Smith, M A (1985)
We report a case of vertebral osteomyelitis caused by Pseudomonas cepacia in a patient with a history of intravenous-drug abuse. P. cepacia infections are usually nosocomial, although community-acquired infections occur more commonly in intravenous-drug abusers than in the general population. Vertebral osteomyelitis caused by P. cepacia has not previously been reported.